Early correction of unilateral scissor bite using transforce appliance and modified twin block appliance - Harshal Chandorikar; Arun Nagrik; Wasundhara A Bhad; Santosh J Chavan; Umal H Doshi (Wolters Kluwer Medknow Publications, 2017)
Early treatment of scissor bite has been advocated mainly to prevent function jaw shift that can eventually lead to permanent skeletal asymmetry and temporomandibular joint pathosis. Although unilateral scissor bite is more common, most of the times, bilateral mandibular expansion is indicated. Lingual transforce appliance can be useful in such cases. This article presents a patient with unilateral scissor bite in mixed dentition with alveolar narrowing. Transforce appliance was used for scissor bite correction followed by modified twin block appliance for stabilization and settling of occlusion till the eruption of premolars. The case was finished with fixed mechanotherapy. Two years after completion of treatment, results were well maintained. Our results suggest that lingual transforce appliance along with careful management of occlusion is effective in the early management of severe unilateral scissor bite.